Analisis Jabatan dalam Manajemen Sumber Daya Manusia: Systematic Literature Review terhadap Peran dan Implementasinya - Hiqmatul Maulidiya; Mohammad Rafi Shidqi; Hanif Achmad Shohiburriyadh; Mualimin Mualimin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Job analysis is a key component of human resource management that plays a role in determining the tasks, responsibilities, and competencies required for a particular job. In various organizations, job analysis serves as the foundation for HR planning, recruitment, selection, employee placement, and performance evaluation. However, research on job analysis remains scattered across various studies focused on specific organizational contexts, necessitating a literature synthesis to gain a more comprehensive understanding of research developments in this field. Therefore, this study aims to analyze the development of research on job analysis and identify its role and contributions to human resource management. This study employed a literature review method by searching for scientific articles in the Google Scholar database using the Publish or Perish (PoP) application with the keyword “job analysis.” The initial search yielded 30 scientific articles, which were then screened based on topic relevance, open access, and publication years ranging from 2020-2026, resulting in 16 articles selected for further analysis. The findings indicate that the literature on job analysis can be grouped into three main themes: the role of job analysis in human resource management, its contribution to improving employee performance and productivity, and its implementation in employee placement and organizational governance. Overall, job analysis has proven to be a strategic tool for enhancing the effectiveness of human resource management. Further research is recommended to examine the implementation of job analysis in greater depth across various organizational contexts to enrich the development of human resource management theory and practice.